Cephalometric Characteristics of Bimaxillary Protrusion in Adolescents - Afnan J Ismael (University of Mosul, College of Dentistry, 2012)
Aims:The purpose of this study was to identify the cephalometric features of bimaxillary protrusion in adolescents. Materials and Methods: Ninty four students were selected aged (12-15) years from secondary schools in Mosul City.Fourty four with class I biprotrusion which were chosen to have an inte-rincisal angle less than 110o, and 50 with class I normal occlusion. Astandardized lateral cephalometric radiograph was taken for each student, sixteen variables, (9 angular and 7 linear) were used in this study. Results: Significant differences were seen in the majority of the linear and angular measure-ments used in this study, the total anterior facial height, lower anterior facial height, upper anterior den-tal height , lower anterior dental height, the angle defines the anteroposterior position of maxilla in re-lation to anterior cranial base, the angle indicates the anteroposterior position of the mandible in rela-tion to the anterior cranial base, mandibular plane angle, palatomandibular plane angle, gonial angle, the angulation of upper central incisor to anterior cranial base and the angulation of lower central inci-sor to mandibular plane were significantly higher in bimaxillary protrusion than normal occlusion in both sexes and total sample.No significant differences were seen in other measurements : upper ante-rior facial height, posterior facial height, ramus height and the angle of palatal plane inclination in rela-tion to anterior cranial base.Interincisal angle was significantly smaller in bimaxillary protrusion than normal occlusion. Conclusions: Most of the anterior facial measurements were significantly higher in bimaxillary protrusion than normal occlusion if compared to posterior facial height and ramus height due to the downward and backward rotation of the mandible in bimaxillary protrusion.